Minimal CR-submanifolds of a six-dimentional sphere - M. Hasan Shahid; S. I. Husain (International Journal of Mathematics and Mathematical Sciences)
We establish several formulas for a 3-dimensional CR-submanifold of a six-dimensional sphere and state some results obtained by making use of them.